Supply Chains’ Failure in Workers’ Rights with Regards to the SDG Compass: A Doughnut Theory Perspective - Maryam Lotfi (MDPI AG, 2021)
Many supply chains have pledged to prevent the violation of workers’ rights as part of social sustainability in their far-flung supply chains. This paper provides a way to understand why supply chains fail to overcome the violation of workers’ rights by mapping the UN SDGs onto the social foundations of the doughnut model, with respect to workers’ rights in supply chains. We develop the sustainable supply chain doughnut model with regards to the SDGs, through which we investigate workers’ rights violations. Examples from both UK-based and world-wide supply chains illustrates our conceptual model. Supply chains have shortfalls in all aspects of the social foundation when it comes to workers as one of their main stakeholders. Until supply chains are successful in overcoming shortfalls across all elements of the social foundation, moving to the next layer of the doughnut framework is impossible, which is the safe and just space for all humans, including workers. This ‘safe and just space’ seems out of reach despite international efforts such as the SDGs. The resulting conceptual model can be the foundation for descriptive, instrumental, and normative research on workers’ rights in the supply chain as part of the social sustainability.